Intrathoracic Testicular Ectopia in Congenital Diaphragmatic Hernia - Mehran Hiradfar; Sadegh Sadeghipoor (Asian Journal of Surgery, 2006)
Congenital diaphragmatic hernia (CDH) is a defect in the diaphragm through which intra-abdominal and retroperitoneal organs may pass. However, the presence of the testis in the thoracic cavity is rare. Here, we describe a case of left-sided Bochdalek CDH with herniation of the left testis through the defect into the thorax, which was managed successfully by primary orchiopexy.